2017
DOI: 10.1007/s11676-017-0449-9
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of traditional land-use and deforestation: a case study of an adat forest in the Kandilo Subwatershed, East Kalimantan, Indonesia

Abstract: Deforestation issues are more problematic when indigenous (adat) communities, living within a forest, have lived there for many generations. These adat communities, who employ traditional land-use, are frequently accused of encroaching on the forest. To understand existing and future trends in the spatial patterns of the expansion of traditional land-use and deforestation, we conducted a case study in the Kandilo Subwatershed using mixed methods with image interpretation, spatial modelling and sociocultural su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
2
22
0
1
Order By: Relevance
“…This study also found that customary law, regulating traditional land-use, played an essential role in controlling deforestation and land degradation (see Figure 1). We conclude that the integration of land allocation, improved farming practices, and enforcement of customary law are effective measures to enhance traditional land productivity while avoiding deforestation and land degradation [7]. Concerning the effectiveness of forest resources protection managed by indigenous peoples, we used the World Resource Institute study to compare the efficacy of using customary law in forest management in Bolivia, Brazil, and Columbia.…”
Section: Introductionmentioning
confidence: 99%
“…This study also found that customary law, regulating traditional land-use, played an essential role in controlling deforestation and land degradation (see Figure 1). We conclude that the integration of land allocation, improved farming practices, and enforcement of customary law are effective measures to enhance traditional land productivity while avoiding deforestation and land degradation [7]. Concerning the effectiveness of forest resources protection managed by indigenous peoples, we used the World Resource Institute study to compare the efficacy of using customary law in forest management in Bolivia, Brazil, and Columbia.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia's rate of deforestation reached 1.3 million per year between 2000 and 2012 (Wegscheider et al 2018). The primary factor causing forest deforestation includes the expansion of small-scale agriculture (Mutolib et al 2017;Austin et al 2019), oil palm plantation (Eldeeb et al 2015, Vijay et al 2016), illegal logging (Khalid et al 2019), corruption (Eldeeb 2015;Pachmann 2018), granting of forest concession (Santika et al 2017;Chen 2019), and human settlement (Nugroho et al 2018;Husodo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The other problem is the shift in farming patterns. From our observations, we found that the need for cash has changed the villagers' behavior (Nugroho et al, 2017) . Many farmers have started to cultivate rubber or oil palm crops mixed with upland rice.…”
Section: Financial and Technical Capacity Of The Adat People In Implementioning
confidence: 79%
“…From ADAT land-use expansion patterns from 1992 to 2012, we found that the need for cash has changed the behavior of villagers towards nature, including that of the ADAT people. Following road construction and a boom in industrial tree production (rubber and oil palm) in the early 2000s, there was a change in the social conditions of the community around MLPF Nugroho et al, 2017;Wahyuni, 2011). Farmers in Rantau Layung as well as Muluy started to cultivate industrial crops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation